Value of dermatology hospital conference as a continuing medical education‐accredited activity: A retrospective review - Ganesh B. Maniam; Nasro Isaq; David A. Wetter; Hafsa M. Cantwell; Marian T. McEvoy; Rokea A. el‐Azhary; Afsaneh Alavi; Michael J. Camilleri; Mark D. P. Davis; Julio C. Sartori‐Valinotti (Wiley, 2024)
Abstract Background Dermatology grand rounds are popular educational activities among dermatologists and trainees, contributing to improved knowledge and skills. Dermatology hospital conferences at Mayo Clinic Dermatology are separate from dermatology grand rounds in that they focus on inpatient consultations and dermatology admissions. Objectives This study aimed to determine the types of cases presented during dermatology hospital grand rounds and evaluate the educational value of this continuing medical education (CME)‐accredited activity. Methods This retrospective study reviewed all inpatient dermatology cases presented during hospital grand rounds at Mayo Clinic Dermatology in Rochester, MN from 2019 to 2022; this study also reviewed the compiled surveys of faculty participants at our institution from 2019 to 2022. Results A total of 389 cases met the inclusion criteria for analysis. The most common diagnostic category was inflammatory/autoimmune diseases (157 cases, 40%), followed by infection or infestation (73 cases, 19%), drug‐induced eruptions (49 cases, 13%), neoplastic or metastatic diseases (41 cases, 11%), genetic/congenital disorders (21 cases, 5%), depositional/nutritional/metabolic conditions (15 cases, 4%) and wound/traumatic/iatrogenic dermatoses (12 cases, 3%), which were the least common. Most cases were presented for discussion of diagnosis and management (246 cases, 63%), but others focused on the arrival of diagnosis (119 cases, 31%) or management alone (24 cases, 6%). The compiled surveys of faculty participants (n = 50) indicated high satisfaction with dermatology hospital grand rounds, with the majority expressing that evidence‐based research was incorporated and positively impacted their practice. Most respondents indicated that hospital conference participation improved knowledge (97%), competence (64%), clinician performance (54%), patient outcomes (52%) and team performance (50%). Conclusions The cases presented during these conferences spanned from challenging inflammatory diseases to simple dermatoses, with over 800 literature references reviewed. Dermatology hospital grand rounds provide high value as a CME‐accredited activity for dermatology faculty, even for those without a specific interest in hospital/inpatient dermatology.